Peace Studies for Sustainable Development in Africa Conflicts and Peace Oriented Conflict Resolution - Spiegel, Egon.; Mutalemwa, George; Liu, Cheng; Kurtz, Lester R. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents a snapshot of a major challenge, and shares subjective views on various areas of conflict in Africa and the diverse - theoretical and practical - efforts to achieve peace. Following an essential review of several real-world conflict contexts on the African continent and attempts to come to terms with them critically as a first step, the book explores the lessons learned to date with regard to peace studies in Africa.
Keywords: Peace; Economic development; Africa-Politics and government; Terrorism; Political violence; Religion and politics; Ethnology-Africa.; Culture; Peace and Conflict Studies; Development Studies; African Politics; Terrorism and Political Violence; Politics and Religion; African Culture